(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The dismantling of a Roman-era wall structure, identified in Calvatone-Bedriacum during the UniMi excavations, made it possible to observe its composition and building characteristics in detail. The study highlights how this structure was built according to techniques that can be classified in the typology developed by A. Bacchetta, but with some specific precautions and particularities.